La construcción de la democracia escolar (2016)
Globalization is providing the school with the historic opportunity to recover its mission relating to the training of citizens well through the experiences that it has begun to develop as a result of the constitutional mandate, they have begun to have institutional presence in the school governments and with them comes with the implementation of processes to re-discover the subject and, in that sense, it open spaces aimed at the formation of subjects with political will,experiences of political participation and expressions of democratic coexistence, which requires an assessment for their orientation and strengthening.